Application of Structural Equation Modeling in Determination of Factors Related to Vasomotor Symptoms (Hot Flashes and Night Sweats) in Women Aged 42-60 Years in Mashhad - Fahimeh Hoseinzadeh; Habibollah Esmaily; Azadeh Saki; Jamshid Jamali; Fatemeh Tara (Mashhad University of Medical Sciences, 2020)
Introduction: Vasomotor symptoms such as hot flashes and night sweats occur in the near-menopausal stage and thereafter and affect women's quality of life. This study was performed with aim to determine the factors related to the severity of vasomotor symptoms using structural equation modeling in women of Mashhad. Methods: This cross-sectional, descriptive-analytical study was performed in 2017 on 664 women aged 42-60 years old in Mashhad. Information about hot flashes, night sweats, depression, anxiety and cognitive impairment were measured through MSSI-38 questionnaire. Demographic data as well as nutrition and life events questionnaires were completed for participants. Data were analyzed with weighted least squares estimation method in Structural Equation Modeling using SPSS software (version 16) and Mplus (version 6.12). P Results: The frequency of hot flashes was moderate in 109 women (%16.40), severe in 84 (%12.70) and very severe in 98 (%14.80). The frequency of night sweats was moderate in 88 women (%13.30), severe in 72 women (%10.80) and very severe in 93 women (%14.00). There was significant relationship between life events (p=0.025), anxiety (p=0.013), disease (p=0.005) and menopause status (p<0.001) with vasomotor symptoms. Conclusion: Participation in training and counseling sessions on reducing stress and increasing women's self-efficacy, controlling underlying diseases by early visiting a specialist, exercising, mobility and improving economic status can be effective in reducing vasomotor symptoms.